B-Type Natriuretic Peptide Concentrations, COVID-19 Severity, and Mortality: A Systematic Review and Meta-Analysis With Meta-Regression - Zinellu, Angelo; Sotgia, Salvatore; Carru, Ciriaco; Mangoni, Arduino A. (Frontiers in Cardiovascular Medicine, 2021)
Alterations in cardiac biomarkers have been reported in patients with coronavirus disease 2019 (COVID-19) in relation to disease severity and mortality. We conducted a systematic review and meta-analysis with meta-regression of studies reporting B-type natriuretic peptide (BNP) or N-terminal proBNP (NT-proBNP) plasma concentrations in COVID-19. We searched PubMed, Web of Science and Scopus, between January 2020 and January 2021, for studies reporting BNP/NT-proBNP concentrations, measures of COVID-19 severity, and survival status (PROSPERO registration number: CRD42021239190). Forty-four studies in 18,856 COVID-19 patients were included in the meta-analysis and meta-regression. The pooled results showed that BNP/NT-proBNP concentrations were significantly higher in patients with high severity or non-survivor status when compared to patients with low severity or survivor status during follow up (SMD 1.07, 95% CI 0.89 to 1.24, p<0.001). Extreme heterogeneity between studies was observed (I2=93.9%, p<0.001). Sensitivity analysis, performed by removing each study in turn and re-assessing the pooled estimates, showed that the magnitude and direction of the effect size was not modified (effect size range, 0.99 to 1.10). No publication bias was observed with the Begg's (p=0.26) and Egger's (p=0.40) t-tests. In meta-regression analysis, the SMD was significantly and positively associated with D-dimer (t=2.22, p=0.03), myoglobin (t=2.40, p=0.04), LDH (t=2.38, p=0.02), and procalcitonin (t=2.56, p=0.01) concentrations. Therefore, higher BNP/NT-proBNP plasma concentrations were significantly associated with severe disease and mortality in COVID-19 patients.